2022
DOI: 10.1002/eqe.3792
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the behaviour factors proposed in the second generation of Eurocode 8 for cross‐laminated timber buildings

Abstract: After 20 years since the publication of the Eurocodes, in 2012, the European Commission gave mandate to the European Committee for Standardization (CEN) to develop a second generation of Eurocodes. Among the different parts of Eurocodes, a substantial revision process has been undertaken for the seismic design rules of timber buildings included in Eurocode 8 (EC8). In particular, a major effort has been made to implement the design rules for Cross‐Laminated Timber (CLT) buildings and to define the behaviour fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Sustainable forestry practices [70] and certifications [71] play a role in ensuring the environmental benefits of CLT. (f) Building codes and standards [72][73][74][75]: The development and updating of building codes and standards related to mass timber construction, including CLT, have been ongoing. As CLT becomes more widespread, regulatory frameworks will adapt to ensure safety and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable forestry practices [70] and certifications [71] play a role in ensuring the environmental benefits of CLT. (f) Building codes and standards [72][73][74][75]: The development and updating of building codes and standards related to mass timber construction, including CLT, have been ongoing. As CLT becomes more widespread, regulatory frameworks will adapt to ensure safety and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…The authors extended the proposal to multi-storey buildings, identifying panel-to-panel connections and hold-downs as dissipative connections, while requiring angle brackets to remain elastic. As a result of research efforts in Europe, a comprehensive CD approach was developed and proposed for inclusion in the next generation of Eurocode 8 [5]- [8]. Based on the proposal, CLT shearwall buildings can be classified into two levels of ductility, namely: medium ductility, which refers to buildings constructed from single panel or multi-panel CLT shearwalls that behave monolithically, and high ductility, which refers to multi-panel CLT shearwalls behaving in coupled-panel (CP) kinematic mode and where the panel-to-panel connections are designed to dissipate energy.…”
Section: Figure 1: Example Of a Multi-panel Clt Shearwallmentioning
confidence: 99%
“…represents the ratio of the wall's bending moment resistance when hold-down yields to the bending moment acting at the base of the shearwall, and it can be obtained using Equation ( 6) ( 6 ) The wall's bending moment resistance when hold-down yields can also be calculated using Equation (7) ( 7 ) The bending moment resistance of the shearwall, , can be expressed as the wall's bending moment resistance when hold-down yields, , which is required to be equal to or greater than the bending moment acting at the base of the shearwall due to the applied lateral loads. ( 8 ) Finally, the non-dissipative elements are required to be capacity-protected. For example, the resistance of the CLT panels, is required to be equal to or greater than the applied shear load at the base of the shearwall when hold-down yields, considering the appropriate overstrength factor, as shown in Equation (9) (9)…”
Section: Capacity-based Design Requirementsmentioning
confidence: 99%
“…Over the last decade, various application examples of CLT could be found worldwide, like the 18-story building Mjøstårnet, completed in Brumunddal, Norway [2]. As for the codification, European Committee for Standardization (CEN) drafted the second generation of Eurocode in 2012 [3], in which much work has gone into implementing the design rules of the CLT structure. Therefore, it can be observed that CLT structures have positive development prospects, and it is meant to improve the learning of the work properties of CLT structures and their components.…”
Section: Introductionmentioning
confidence: 99%